Nutrition interventions improve anemic status in male college long-distance runners - Kazami, K.; Ashida, K.; Sato, Y.; Arai, T.; Kazami, T.; Ohsaki, S.; Kobayashi, S. (Japanese Journal of Physical Fitness and Sports Medicine, 2014)
College athletes often tend to suffer from defective nutrition status due to excessive physical training with inadequate dietary intakes, which resulted in various physical disorders such as anemia. This study was conducted to investigate the effects of nutrition interventions to the anemic state of long distance runners. A nutritional education program was applied and daily single pack of nutritional supplement drink rich in iron, zinc, copper, selenium as well as eleven vitamins were provided for two months. Blood hemoglobin, red blood cells as well as serum ferritin and iron levels after the intervention were significantly higher compared with the basal, pre-intervention level of respective items. Among the subjects, two were found to be anemic (hemoglobin<13g/dl) before the intervention. Both of them, however, were successfully recovered to normal status (hemoglobin >/= 13g/dl) thereafter. The pre-intervention levels of hemoglobin were negatively correlated to the amount of difference between those of pre- and post-intervention, which appeared to indicate an improvement of nutrient deficiency that caused the hypochromia. On the other hands, the intake of energy and nutrients from meals did not change before and after the intervention. From the results obtained, it seems to be appropriate to emphasize the importance of nutrition education, especially, a possible effectiveness of including multiple nutrient supplementation in nutrition program for college athletes is suggested.